Mothers’ views on the school-starting process for deaf children - Işıkdoğan Uğurlu, Necla; Kayhan, Nilay; Hakkoymaz, Sakine (Frontiers in Psychology, 2026)
Early diagnosis, hearing aid implementation, education, and active family participation play an important role in hearing loss. Cochlear implantation, hearing support technologies, and auditory rehabilitation are essential components of early intervention. Difficulties experienced by families of children with hearing loss from birth may negatively affect the children’s development. This study aims to examine the early childhood school-preparation journeys of children with hearing loss through their mothers’ voices. Using a qualitative research method, this study was conducted with 20 mothers of children with hearing loss. Demographic information forms and interview questionnaires were used as data collection tools. Semi-structured face-to-face interviews were conducted with the mothers. The data were analyzed using content analysis. Four main themes emerged: “realization and guidance, family life changing with diagnosis and search for empowerment, holistic support for children with HL, and sustainable and accessible support mechanisms.” The mothers emphasized that newborn hearing screening plays an important role in early diagnosis and intervention and that they require informational, social, and financial support following their child’s hearing loss diagnosis. They reported that they receive most of their support from family members and from other families with children who have hearing loss, while also expressing a lack of broader social support. One of the most striking findings is that families need information and support not only on the implementation of hearing aids for children diagnosed early but also on the communication method to be used.